2018
DOI: 10.3390/fractalfract2010004
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Velocity as a Tool for the Study of Non-Linear Problems

Abstract: Singular functions and, in general, Hölder functions represent conceptual models of nonlinear physical phenomena. The purpose of this survey is to demonstrate the applicability of fractional velocities as tools to characterize Hölder and singular functions, in particular. Fractional velocities are defined as limits of the difference quotients of a fractional power and they generalize the local notion of a derivative. On the other hand, their properties contrast some of the usual properties of derivatives. One … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Everywhere, will be considered as a small positive variable. The asymptotic small O notation will be used as introduced in [5]. Definition 1.…”
Section: General Definitions and Conventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Everywhere, will be considered as a small positive variable. The asymptotic small O notation will be used as introduced in [5]. Definition 1.…”
Section: General Definitions and Conventionsmentioning
confidence: 99%
“…What was not recognized at that time was the inherent asymmetry of such definition, which lead to the misplaced expectation that the left and right velocities should be equal. Fractional velocities were used to characterize the growth of some singular functions [5]. Therefore, it is of interests to establish its relationship with the indicial derivative.…”
Section: Characterization Of Fractional Velocitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was established that for fractional orders fractional velocity is continuous only if it is zero. The properties of fractional velocity are surveyed in [11].…”
Section: Fractional Velocitymentioning
confidence: 99%
“…FO systems have found wide applications in physics and control [12][13][14]. It has been demonstrated that a singular function can represent the conceptual models of nonlinear physical phenomena accurately [15] and can be extended to processes related with natural phenomena, such as epidemiology [16]. Nevertheless, it is not simple to handle the fractional operator computationally.…”
Section: Introductionmentioning
confidence: 99%